2019
DOI: 10.1159/000500133
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the pH Value of Refluxate and Proximal Extent on Heartburn Perception in Patients with Proton Pump Inhibitor-Refractory Non-Erosive Reflux Disease

Abstract: Background and Objectives: Weakly acidic reflux has been reported as the major cause of symptom occurrence in patients with proton pump inhibitor (PPI)-refractory non-erosive reflux disease (NERD). This study is aimed at clarifying whether the pH value of weakly acidic reflux affects the induction of symptoms. Methods: We retrospectively evaluated the records of combined multichannel intraluminal impedance and pH monitoring in 57 patients with PPI-refractory NERD. Weakly acidic refluxes were divided into 3 cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Along the same lines, several studies have reported that weakly acidic reflux is one of the most relevant underlying causes of PPI-refractory NERD (for review see [96]). In addition, it was shown that the reflux events at pH 4-5, reaching the proximal esophagus, were the main symptom trigger in these patients [97]. Indeed, the pH of weakly acidic reflux represents a determining factor in provoking heartburn [98].…”
Section: Vonoprazan For Gerd: Conclusionmentioning
confidence: 97%
“…Along the same lines, several studies have reported that weakly acidic reflux is one of the most relevant underlying causes of PPI-refractory NERD (for review see [96]). In addition, it was shown that the reflux events at pH 4-5, reaching the proximal esophagus, were the main symptom trigger in these patients [97]. Indeed, the pH of weakly acidic reflux represents a determining factor in provoking heartburn [98].…”
Section: Vonoprazan For Gerd: Conclusionmentioning
confidence: 97%
“…Thus, the importance of strong acid suppressive therapy in patients with troublesome reflux symptoms despite PPI use has not been elucidated fully, and no study has evaluated the relationship between changes in the pH value of the refluxate and symptom induction after switching from PPI to VPZ using MII-pH monitoring. We previously reported that reflux at pH < 5 was the major cause of symptom occurrence in patients with PPI refractory NERD while taking double-dose PPI [8]. Therefore, we presumed that by switching to VPZ, which is expected to have a stronger acid suppressive effect than conventional PPI, the ratio of reflux at pH < 5 would decrease, and the troublesome reflux symptoms would improve.…”
Section: Discussionmentioning
confidence: 98%
“…However, few studies have focused on whether the frequency of reflux symptoms differs according to the pH value of weakly acidic reflux. Recently, we reported that reflux at pH 4-5 was the main factor that induced symptoms in patients with PPI-refractory NERD who underwent double-dose PPI [8]. Therefore, we thought that maintenance of the pH value of the refluxate at ≥5 could improve the symptoms of patients with PPI-refractory NERD.…”
Section: Introductionmentioning
confidence: 99%
“…PGE 2 is involved in the induction of heartburn symptoms 14,26 . Interestingly, heartburn symptoms were most frequently reported when weak acid was refluxed, especially at pH 5, in patients with PPI-refractory GERD 10,11 . Moreover, the administration of weak acids (pH 4-5) induced heartburn symptoms in nearly 50% of patients with GERD symptoms 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Advanced techniques for the measurement of oesophageal pH have shown that reflux events with values other than pH < 4, such as weak acids (i.e., pH 4-7), are possible responsible substances related to various GERD symptoms 7 . Several studies have reported that weak acids contribute to the pathogenesis of GERD symptoms in patients with proton pump inhibitor (PPI)-refractory GERD, which are considered problematic among the majority of clinicians [8][9][10][11][12] . Despite recent evidence for the role of weak acid reflux, the degree of risk and mechanisms by which it leads to GERD-related symptoms remain unclear.…”
mentioning
confidence: 99%